Function of a pathway-associated major facilitator superfamily gene hsaf-orf1 in the biosynthesis of the antifungal HSAF in Lysobacter enzymogenes. (9th January 2023) - Yue, Huan; Du, Liangcheng
Abstract: HSAF is a potent antifungal natural product with a structure distinct from the antifungal drugs or fungicides in use. The biosynthesis and regulation of HSAF and its analogs have been subject to extensive studies, but the transport of the compounds is still not very clear. In Lysobacter enzymogenes OH11, hsaf-orf1 is the first gene of the HSAF biosynthetic gene cluster (BGC) and has been predicted to encode a major facilitator superfamily (MFS) transporter. We in-frame deleted hsaf-orf1 in strain OH11 and analyzed the metabolite profiles in the total, extracellular and intracellular extracts. The results showed that there was not a significant difference in the distribution of HSAF and its analogs in the ΔORF1 mutant versus in the wild type. Culture media supplemented with glucose or N -acetylglucosamine (GlcNAc) dramatically induced the production of HSAF and analogs in the wild type, but not in ΔORF1. Using fluorescence-labeled glucose 2-NBDG (2-deoxy-2-[(7-nitro-2, 1, 3-benzoxadiazol-4-yl) amino]-d -glucose), we showed that the sugar transport was significantly impaired in ΔORF1. Further analyses by qRT-PCR (quantitative reverse transcription polymerase chain reaction) of a series of key genes for HSAF biosynthesis and regulation supported that hsaf-orf1 is indeed involved in the import of the sugar into OH11. Together, the study unveiled that hsaf-orf1 plays an important role in the regulation and biosynthesis of HSAF and its analogs, through controlling the import of small sugars, which could serve as nutrients as well as signals to induce the antifungal production.